Microfinance and Violence Against Women in Rural Guatemala - Cepeda, Isabel Vilares (Journal of interpersonal violence, 2021)
Violence against Women (VaW) has come to be recognized as a serious human rights abuse with important consequences not only for women but for whole societies. Since VaW has several manifestations, it is possible to differentiate among different types of violence. In this article, a broad theoretical framework with different dimensions of gender violence was adapted to a Latin American social and cultural context to measure three out of the five main types of violence: economic violence, emotional psychological violence, and coercive control. The goal of this article is to provide empirical evidence to determine whether access to microfinance services plays a role in reducing VaW. To this end, we designed and performed a cross-sectional study with a treatment and a control group in rural Guatemala. A sample of 883 rural women in the “Altiplano” area of Guatemala (448 women with microfinance services and 435 without) was surveyed from May to November 2012. The results of the bivariate logistic regression showed evidence of association between access to microfinance services and reduction of VaW. After adjusting for covariates, global, economic, and emotional psychological violence maintained a negative and statistically significant association with microfinance, while only coercive control showed no statistical association with microfinance services. Access to microcredits showed a very clear relationship to reducing economic and emotional violence but not coercive control, a factor that may be determined by social and cultural norms. In contrast to Status Inconsistency Theory, which has been tested primarily in Asia, our study of Guatemala showed that increased status and economic independence of women due to their participation in microfinance services reduced VaW.